The influence of product quality on purchase decisions and its impact on consumer satisfaction - Heri Prabowo; Farah Chalida Hanoum; Qristin Violinda; Hawik Ervina Indiworo; Rita Meiriyanti (University of Merdeka Malang, 2026)
This study aims to analyze the influence of product quality on purchase decisions and its impact on consumer satisfaction at Whitebon Resto Semarang. In an era of increasingly intense business competition, understanding the factors that influence consumer purchasing decisions is crucial for maintaining competitiveness and customer loyalty. The research problem addressed in this study is how product quality affects purchasing decisions and how these decisions subsequently influence consumer satisfaction. The proposed research method employs a survey approach, involving respondents who are customers of Whitebon Resto Semarang. Data were collected using structured questionnaires to capture consumers’ perceptions of product quality, purchasing decisions, and satisfaction levels. The findings reveal a significant positive relationship between product quality and purchasing decisions. Furthermore, purchasing decisions were found to have a meaningful contribution to enhancing consumer satisfaction. These results highlight the pivotal role of product quality in driving consumer decision-making and satisfaction. The implications of this study suggest that the management of Whitebon Resto Semarang should prioritize continuous improvement in both product quality and service performance to maintain and strengthen consumer satisfaction and loyalty in the long term.